OPTIMALISASI STRATEGI MENGAJAR REGULASI DIRI DALAM BELAJAR BAGI PENDIDIK SMA X - Isaputra, Samuel Adiprasetya; V. Bolang, Caroline Mathilda; C. Purnomo, Patricia Audrey; Lidiawati, Krishervina Rani (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
SMA X, located in Yogyakarta, is committed to providing quality education to its students, the majority of whom come from outside Java, particularly from Eastern Indonesia. In addition to its educational responsibilities, SMA X faces challenges such as students from broken homes, economic and social issues, and a lack of teachers skilled in counseling and handling students with personal issues. These challenges negatively impact students' academic performance. The Community Service Team conducted teachers training on self-regulated learning teaching strategies and basic counseling focusing on emotion regulation strategies. Workshops, group discussions, and practical exercises were employed during the training, and significantly improving teachers' cognitive understanding, with average scores increasing from 46.9 to 70.3. Behaviorally, some teachers began implementing strategies such as offering task choices to enhance student motivation and teaching students to plan and monitor their task completion processes. Continuous evaluation and mentoring are ongoing to ensure the optimal implementation of the training material. Additionally, SMA X has been designated as a mentored school to more effectively address its challenges.